Combination therapy using trans-catheter aortic valve implantation and adaptive servo-ventilation in patient with aortic stenosis and heart failure. Issue 5 (May 2021) - Imamura, Teruhiko; Hori, Masakazu; Tanaka, Shuhei; Fukuda, Nobuyuki; Sobajima, Mitsuo; Ueno, Hiroshi; Kinugawa, Koichiro
Abstract: Severe aortic stenosis sometimes accompanies advanced heart failure with reduced cardiac contractility (i.e. low-flow low-gradient aortic stenosis). The therapeutic strategy for the remaining heart failure following trans-catheter aortic valve implantation remains unknown. An 84-year-old man with six hospitalizations due to aortic stenosis and congestive heart failure with reduced ejection fraction was admitted to our institute. Heart failure remained following trans-catheter aortic valve implantation. Additional adaptive servo-ventilation therapy with optimal pressure setting determined by the ramp test further improved his heart failure symptoms. Combination therapy using trans-catheter aortic valve implantation and adaptive servo-ventilation might be a promising therapeutic tool to ameliorate heart failure with severe aortic stenosis. <;Learning objective: Adaptive servo-ventilation might be a promising therapy in patients with persistent congestive heart failure following trans-catheter aortic valve implantation for severe aortic stenosis.>